EFFECT OF SHORT TERM RAJYOGA MEDITATION ON ANXIETY AND DEPRESSION - –, Kiran; –, Chalana; Arora, Anterpreet K; Girgila, Kawalinder K (Pakistan Journal of Physiology, 2014)
Background: With the current globalisation of the world’s economy and demands for enhanced performance, stress is present universally. Life’s stressful events, anxiety and depression cause both deleterious and cumulative effects on the human body. The practice of meditation might offer a way to relieve that stress. This study was designed to determine the effectiveness of a group stress reduction program based on Rajyoga meditation for patients with anxiety and depression. Method: The study was conducted on 100 patients suffering from anxiety and depression who were on similar drug regime. They were randomised into two groups; Meditators (n=50; age 34.12±9.05 years) and controls (n=50 age 33.68±10.78 years). The meditators were taught Rajyoga meditation and practised for 20 min/day, 7 d/week for 6 weeks. The control group did not practice any type of meditation. Results were assessed by using Hamilton anxiety and depression scales. Results: The patient with anxiety and depression symptoms in intervention group and control group showed significant improvement following six weeks of intervention as suggested by significant reduction in scores of HAM-A (p<0.001) and HAM-D (p<0.001). However, the percentage of relief was more in intervention group as compared to control group. Conclusion: A short-term, yoga-based lifestyle intervention may significantly reduce anxiety and depression and improve subjective well-being and personality. Pak J Physiol 2014;10(1-2):18–2